PHYSICAL EDUCATION: PROMOTING GROWTH AND DEVELOPMENT FOR A QUALITY LIFE WITH THROUGH MATROGINÁSTICA (Fiep Bulletin - online, 2011)
The study is a survey of the Interdisciplinary Group for Study and Research of the Body and Movement - GIEPCOM, Course of Physical Education Degree Mode of Regional Integrated University of High Uruguay and Missions, Campus de Frederico Westphalen, RS, in the line of research, Cultures Body and Education through Movement. The theme is MATROGINÁSTICA: Physical Education: Promoting Growth and Development for a Quality Life with through Matroginástica. The goal is to investigate the interaction with intra-family practices Matroginástica - activities between parents and children in schools through playful activities. The research problem: it is possible to approach the family of the school, promoting teaching and learning helping to build human values of students through Matroginástica? This qualitative research / descriptively. Actors research: children and adolescents from kindergarten and elementary school, parents and teachers from four schools in four counties in the region. The schools were chosen by criteria of representativeness, after application of these activities in a pilot school. Data collection: observation, document analysis, questionnaire. Intention is to highlight new forms of relationship with the school community. Thereby improving dynamic playful at school.
Keywords: Matroginástica; playfulness; family and school